POTGIETER, Daniël Jacobus Inventory of documents - POTGIETER, Daniël Jacobus (ARCA, 2018)
Private papers of D.J. Potgieter, Private Secretary of Dr. D.F. Malan [1941-1943], Financial Secretary NP [1944], Secretary NP Natal [1945-1952], MPC Dundee [1949-1953], MP Vryheid [1953-1966].
COVERAGE 1932-1966; 51 Files; *1,40 Metres.
Keywords: POTGIETER, Daniël Jacobus; Inventories; Politicians; National Party